The Influence of Social Media Marketing and Brand Awareness on Purchase Intention with Brand Image As A Mediating Variable On Red Lotus Villa & Property Management Bali - Ida Ayu Sintha Permata Sari; Irene Hanna H. Sihombing; Ida Ayu Putri Widawati (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze (1) the effect of social media marketing on purchase intention, (2) the effect of brand awareness on purchase intention, (3) the effect of social media marketing on brand image, (4) the effect of brand awareness on brand image, (5 ) the effect of brand image on purchase intention, (6) the effect of social media marketing on purchase intention mediated by brand image, and (7) the effect of brand awareness on purchase intention mediated by brand image at Red Lotus Villa & Property Management. The sampling technique used in this research is purposive sampling. Data were collected by means of a study of documentation and distributing questionnaires to 130 respondents. To analyze the research model in this study using the PLS (Partial Least Square) and SEM method with the SmartrPLS 3.3.3 program as a tool. The results of data analysis show that (1) social media marketing has a positive and significant effect on purchase intention, (2) band awareness has a positive and significant effect on purchase intention, (3) social media marketing has a positive and significant effect on brand image, (4) Awareness brand has a positive and significant effect on brand image, (5) brand image has a positive and significant effect on purchase intention, (6) social media marketing has a positive and significant effect on purchase intention mediated by brand image, and (7) brand awareness has a positive effect and significant to purchase intention mediated by brand image.